EFFECT OF BRAND IMAGE AND SERVICE QUALITY ON CUSTOMER SATISFACTION AND LOYALTY AT BANK JATIM SYARIAH SURABAYA - Putro R.N.C.A.; Rachmat B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The research objective is to examine the effect of brand image on customer satisfaction, examine the effect of service quality on customer satisfaction, and examine the effect of customer satisfaction on customer loyalty. The research hypotheses state that brand image has an effect on customer satisfaction, service quality has an effect on customer satisfaction, and customer satisfaction has an effect on customer loyalty. This research uses survey data from customers of Bank Jatim Syariah Surabaya. The data were collected using a questionnaire from respondents who were customers of Bank Jatim Syariah Surabaya, had at least one account at Bank Jatim Syariah Surabaya, and were at least 17 years old. The hypothesis testing techniques are carried out using SEM analysis with the AMOS program. The research findings indicated that brand image has a positive and not significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty at Bank Jatim Syariah Surabaya. This research showed that there is a positive and not significant correlation between brand image and customer satisfaction because the public knows Conventional Bank Jatim more; so that, Bank Jatim Syariah Surabaya is not yet widely known to the public. In addition, Civil Servants in Surabaya have long been permanent customers of Conventional Bank Jatim. Based on the research findings, the more satisfied customers, the more loyal customers will be at Bank Jatim Syariah.